2016
DOI: 10.1016/j.pjnns.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Spinal tuberculosis with severe neurological symptoms as a complication of intravesical BCG therapy for carcinoma of the bladder

Abstract: The cases described in the work are the first documented reports in the Polish literature of spinal tuberculosis which occurred as a complication of intravesical administration of bacilli Calmette-Guérin. The diagnosis was based on the finding of BCG vaccine bacillus with molecular methods or PCR. Full antimycobacterial treatment was implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Boruah et al (2021) [30] retrospectively evaluated the MRI imaging data of 19 patients with spinal tuberculosis and found that it was very important for the early diagnosis of patients, which was beneficial to reduce the morbidity and severity of patients. Another study retrospectively analyzed the MRI and CT imaging features of spinal tuberculosis and tumors and found that it can be used in the differential diagnosis of spinal tuberculosis and spinal tumors [31], which is consistent with the conclusions of this study. However, spinal tuberculosis and tumors have different manifestations at different stages of disease progression, and special cases may have atypical manifestations.…”
Section: Discussionsupporting
confidence: 87%
“…Boruah et al (2021) [30] retrospectively evaluated the MRI imaging data of 19 patients with spinal tuberculosis and found that it was very important for the early diagnosis of patients, which was beneficial to reduce the morbidity and severity of patients. Another study retrospectively analyzed the MRI and CT imaging features of spinal tuberculosis and tumors and found that it can be used in the differential diagnosis of spinal tuberculosis and spinal tumors [31], which is consistent with the conclusions of this study. However, spinal tuberculosis and tumors have different manifestations at different stages of disease progression, and special cases may have atypical manifestations.…”
Section: Discussionsupporting
confidence: 87%
“…All these patients were male, with a mean age of 73.2 (35-94) years and with a median interval of 1.3 years (0.5 months-12 years) between BCG instillation and the onset of spondylitis. Chronic back pain was the most common complaint, and serious neurological symptoms might occur as a result of neurosurgical spinal cord decompression [58]. BCG spondylitis is thought to develop by hematogenous spread from the deep pelvic veins to the internal vertebral venous plexuses, which may explain its high incidence in the thoracolumbar spine [59].…”
Section: Systemic Complicationsmentioning
confidence: 99%
“…Other articles with M. bovis BCG infection and spinal pain have been published [34][35][36], but they were not consistent with a vertebral osteomyelitis diagnosis. The frequency is possibly underestimated knowing the possible difficulties in documenting such an infection, as in two other publications [27,37].…”
Section: Reviewmentioning
confidence: 98%